A review of the conservation status of Australian mammals - Woinarski, John C.Z.; Burbidge, Andrew A.; Harrison, Peter L. (THERYA, 2014)
Introduction: This paper provides a summary of results from a recent comprehensive review of the conservation status of all Australian land and marine mammal species and subspecies. Since the landmark date of European settlement of Australia (1788), at least 28 of the ca. 272 Australian endemic land mammal species have been rendered extinct. Results and Discussion: Extinctions have occurred at a more or less consistent rate of one to two species per decade since the 1840s, with that rate continuing unabated. A further 55 species from that original fauna are now threatened, and an additional 42 are Near Threatened. Although many factors have contributed to these declines and extinctions, and the array of threats varies amongst individual species, the threat that has had (and is continuing to have) most detrimental impact upon terrestrial mammal species is predation by the introduced cat Felis catusand European red fox Vulpes vulpes. There has been some successful broad-scale management of the fox, but the threat posed by feral cats remains largely unabated. For the 55 species occurring in Australian marine waters, the information base is mostly too meagre to assess conservation status other than as Data Deficient. For the Australian mammal fauna generally, the current conservation management effort is insufficient, with ongoing trends for decline in many species – for example, of 49 species whose conservation status changed over the period 1992-2012, 38 had deteriorating conservation status whereas only 11 had improving status. Key words: extinct, feral cat, fire, marine mammals, marsupial, predation, red fox, threatened, translocation.